Dividend policy, corporate control and the tax status of the controlling shareholder - Christian Andres; André Betzer; Marc Goergen (University of Wuppertal, Schumpeter School of Business and Economics, 2012)
This paper studies the impact of the concentration of control, the type of controlling shareholder and the dividend tax preference of the controlling shareholder on dividend policy for a panel of 220 German firms over 1984-2005. While the concentration of control does not have an effect on the dividend payout, there is strong evidence that the type of controlling shareholder matters as family controlled firms have high dividend payouts whereas bank controlled firms have low dividend payouts. However, there is no evidence that the tax preference of the large shareholder has an impact on the dividend decision.
urn:nbn:de:hbz:468-20120524-102137-5
Keywords: G32; G35; 330; Dividend policy; payout policy; Lintner dividend model; tax clientele effects; corporate governance; Dividende; Eigentümerstruktur; Aktionäre; Familienunternehmen; Steuerplanung; Corporate Governance; Deutschland